ASSESSMENT OF THE PHARMACOLOGICAL EFFICACY OF A NEW ANTI-DIABETIC DRUG - Feruza Kh. Inoyatova; Bakhtiyar U. Iriskulov; Dilshod D. Achilov; Madina A. Shatursunova (Central Asian Journal of Medicine, 2023)
Diabetes mellitus is today one of the global medical and social problems in the health care system. According to the International Diabetes Federation (IDF), there were more than 425 million type II diabetes patients worldwide in 2019. Purpose of the study. To study preclinical pharmacological and toxicological studies of a new drug obtained on the basis and evaluate its hypoglycemic effect. Materials and research methods. The study of the acute toxicity of the new antidiabetic drug was carried out on 20 sexually mature white male rats with an initial body weight of 160-183 grams, exposed to intragastric doses of 500, 550, 600 and 650 mg / kg. The animals were injected intragastrically at 3.0 ml / 100 g. body weight. Research results. Observation of experimental animals with acute toxicity of the herbal preparation for 14 days, there were no pronounced symptoms of intoxication in animals. In groups of 6 animals receiving 550 mg / kg, 1 died, 1 received 600 mg / kg-2, and 650 mg / kg-4. Experienced animals responded adequately to external stimuli. Visible mucous membranes are moist, pale pink in color, shiny and smooth in appearance, no foci of baldness were found.